2016
DOI: 10.1007/s11356-016-8303-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the biochar aromaticity and molecular structures of the chlorinated organic compounds on the adsorption characteristics

Abstract: Adsorption behaviors of the chlorinated organic compounds (COCs) (i.e., trichloroethylene (TCE), 1,2,4-trichlorobenzene (1,2,4-TCB); 1,2-dichlorobenzene (1,2-DCB); and monochlorobenzene (MCB)) by the commercial rice husk-based biochar (RH500) and the laboratory-prepared biochars from corn stalks under different pyrolytic temperatures (i.e., CS300, CS500, CS700) were examined and interpreted by the pseudo-first-order kinetic model, the double layer model with two energies, and the Freundlich model. It is identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(13 citation statements)
references
References 69 publications
0
13
0
Order By: Relevance
“…1 FTIR spectra of BA (A); BN (B) and BK (C) in pyrolysis of 400, 500, 600 and 700 °C are related to the degradation of surface functional groups (Fig. 1) and dehydration, depolymerization, and volatilization processes (Han et al 2017b;. The N content did not vary with pyrolysis temperature.…”
Section: Elemental Compositionmentioning
confidence: 92%
“…1 FTIR spectra of BA (A); BN (B) and BK (C) in pyrolysis of 400, 500, 600 and 700 °C are related to the degradation of surface functional groups (Fig. 1) and dehydration, depolymerization, and volatilization processes (Han et al 2017b;. The N content did not vary with pyrolysis temperature.…”
Section: Elemental Compositionmentioning
confidence: 92%
“…Atomic ratios of elements, including aromaticity (H/C ratio) and polarity (O/C ratio), were essential to evaluate the stability of biochar in the soil [53,63,78]. Therefore, CSB with the low value of the H/C ratio indicated that CSB had high aromaticity with increased resistance in the soil.…”
Section: The Effect Of Pyrolysis and Feedstock On Biochar Propertiesmentioning
confidence: 99%
“…Anionic functional groups such as -OH, -COOH, and -C(=O)H, -CHO formed and occurred on the surface area [30,43,62]. By contrast, the acidic functional groups were removed [39,43,62,63]. Cellulose and lignin degradation and formation of the channel structure increased the surface area and pore volume of biochar [12,16,30,48], while pyrolysis temperature influenced the molecular structure and pores size distribution [30,34,43,48].…”
Section: The Effect Of Pyrolysis and Feedstock On Biochar Propertiesmentioning
confidence: 99%
See 2 more Smart Citations